In vitro micropropogation of Stevia rebaudiana in Bihar - RASHMI, K; SAHAY, S; KUMAR, H (The Indian Journal of Agricultural Sciences, 2019)
The shoot apex, leaf, nodal stem and internodal stem of Stevia rebaudiana (Bert.) Bertoni were cultured on 21 different media, having different concentrations and combinations of auxins (2,4-D, IBA, NAA) and cytokinins (KIN, BA) supplemented to Murashige and Skoog (MS) basal medium. Besides these explants, the formed callus and developed shoots were also cultured. The tissue culture experiments resulted in establishment of cultures, swelling of explants, elongation of existing shoot, callus formation, caulogenesis, rhizogenesis and regeneration of plantlets, acclimatization of plantlets and ultimately development of micropropagation protocol. During acclimatization, the plantlets regained their photosynthetic efficiency and transpiration mechanism. The size of leaf also increased during acclimatization. In the present investigation a survival rate of 48% was found during hardening. Good callus formation and differentiation of shoots from formed callus showed the possibility of plant improvement through tissue culture.